Expression and clinicopathological relevance of Fibroblast Growth Factor Receptors in Canine Mammary Gland Tumors - Sahabi, Kabiru; Selvarajah, Gayathri Thevi; Dhaliwal, Gurmeet Kaur; Sharma, Reuben Sunil Kumar (Unique Scientific Publishers, 2024)
This study was conducted to determine the expression of fibroblast growth factor receptors (FGFRs) in canine mammary gland tumors (CMT) and to investigate the expression relationship with clinical and histopathological parameters. Forty-six CMT tissues were immunohistochemically probed for the expression of FGFR2, FGFR3 and FGFR4 using rabbit polyclonal antibodies. The expression of each receptor was analyzed (Fisher’s exact test) for its relationship with clinical parameters (breed size, age, neuter status, involvement of inguinal mammary gland, number of glands involved) and histopathology (mitotic index, tumor size, tumor grade, PCNA and Vimentin expression). Kaplan-Meier survival and Cox-Regression were performed for survival analysis. The proteins (FGFR2,-3 and-4) were localized to the membrane and cytoplasm. Forty-five tumors (97.8%) expressed both FGFR2 and FGFR3. The FGFR4 was expressed in 42 (91.3%) of the tumors. The expression of FGFR2 was significantly associated with histopathology grade 3 of the tumors (P=0.027). FGFR3 expression was not associated with any clinical or histopathology parameters. FGFR4 expression was associated with large breed dogs (P=0.044), and large tumor size (>3cm) (P=0.045), but none of the proteins expressed predicted post-surgical survival in the dogs. In this study, FGFR2 expression has indicated its usefulness in CMT as an indicator of increased tumor malignancy, while FGFR4 expression has demonstrated the ability to identify high stage tumors. Based on these findings, FGFR2 and 4 can be used as markers for advanced and aggressive CMT. © 2024, Unique Scientific Publishers. All rights reserved.